Exploring The Dimensions Of Retail Store : That Impact To Forming Customer Satisfaction, Trust, And Customer Loyalty - Daniel Widjaja, YB Andre Marvianta, Roseline M. Anwar & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
The numerous retail stores that exist amid public shows a tight competition amongretail store entrepreneurs. As a matter of fact, customers satisfaction is a main keyto survive amid the tough competition. The customer satisfaction can be built aftercustomer evaluates and assesses dimensions in a retail store based on theirshopping experience. This research aims at testing test and discovering whichdimension has potential to lift the customers satisfaction of shopping in a retailstore. The data from our survey has been tested by using Structural EquationModeling (SEM) to confirm our model. The result shows that product and price arethe most fundamental dimensions in forming customers satisfaction and also tobuild trust and loyalty of customers of shopping in the retail store.Keywords : [retail stores; customersâ satisfaction; customersâ loyalty; trust]